2002
DOI: 10.1037/0022-0663.94.2.344
|View full text |Cite
|
Sign up to set email alerts
|

The nature of teachers' pedagogical content beliefs matters for students' achievement gains: Quasi-experimental evidence from elementary mathematics.

Abstract: In a longitudinal study of 496 students in 27 self-contained German elementary school classrooms, performance in mathematical word problems and arithmetic tasks was measured at the end of Grades 2 and 3. A questionnaire was used to assess the degree to which teachers' pedagogical content beliefs in elementary mathematics reflect a cognitive constructivist orientation, rather than an associationist or direct-transmission view of learning and teaching. Our findings show that a cognitive constructivist orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
2
83

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(271 citation statements)
references
References 19 publications
9
177
2
83
Order By: Relevance
“…between students) for individual, active cognitive processes (Prawat, 1992). As Staub and Stern (2002) illustrate, a (socio-) constructivist orientation of the teachers is associated with students achieving higher scores in solving mathematical word problems. Other findings support the relevance of teacher constructivist beliefs regarding student learning outcomes in mathematics (Dubberke, Kunter, McElvany, Brunner, & Baumert, 2008;Stipek, Givvin, Salmon, & MachGyvers, 2001).…”
Section: Teacher Beliefs About Learning and Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…between students) for individual, active cognitive processes (Prawat, 1992). As Staub and Stern (2002) illustrate, a (socio-) constructivist orientation of the teachers is associated with students achieving higher scores in solving mathematical word problems. Other findings support the relevance of teacher constructivist beliefs regarding student learning outcomes in mathematics (Dubberke, Kunter, McElvany, Brunner, & Baumert, 2008;Stipek, Givvin, Salmon, & MachGyvers, 2001).…”
Section: Teacher Beliefs About Learning and Teachingmentioning
confidence: 99%
“…Regarding beliefs about the learning and teaching of mathematics, Staub and Stern (2002) distinguish between a transmission view (learning as the result of information transmission and repetition by the learner) and a constructivist or socio-constructivist view. According to the latter, learning depends on the individual's active cognitive processes; moreover, a socio-constructivist view emphasizes the role of social exchange (e.g.…”
Section: Teacher Beliefs About Learning and Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of programmes in the USA (Slavin and Lake 2007) and South Africa (Fleisch and Schöer 2014) indicate that focus on instructional change is most likely to have positive outcomes (Slavin and Lake 2007;Staub and Stern 2002). Research in sub-Saharan Africa suggests that to support teacher learning, modelling and teacher coaching are necessary (Schwille and Dembélé 2007;UNESCO 2012;UNESCO and CASTME 2001).…”
Section: Maths Interventions In Developing Countriesmentioning
confidence: 99%
“…Haney & McArthur (2002) conducted a study investigating two questions pinpointing science teachers' beliefs as constructivists, and to what extent these beliefs correspond with real teaching practices, and concluded that there were in fact two main types of beliefs: central beliefs and peripheral ones. Another study by Staub & Stern (2002) featured a sample of 496 elementary students whose performance and skills in mathematical problem-solving were measured. Their teachers' beliefs toward the cognitive and pedagogical mathematical content were measured as well, concluding that they possessed a set of constructivist beliefs which were strongly correlated with their students' abilities in solving mathematical problem.…”
Section: Literature Reviewmentioning
confidence: 99%